Vaclovo Biržiškos bendražygis Izidorius Kisinas - Zaveckienė, Žiedūnė (Knygotyra, 1997)
In this article, the lesser-known periods of L. Kisinas's life and activities connected with V. Biržiška are revealed. From 1935 to 1941, L. Kisinas worked in the libraries of Kaunas and Vilnius University, both headed by V. Biržiška. During that time, L. Kisinas prepared many bibliographical works such as "Professor Eduardas Volteris's Bibliography" (1928), "Professor Mykolas Biržiška's Bibliography" (1931), "Antanas Smetona's Bibliography and Biobibliography" (1935), and others.However, the most important work, which was not known for a long time, was the work dedicated to A. Smetona. While writing it, L. Kisinas was consulted by V. Biržiška, who also wrote the introduction to this book. In this introduction, there is a very rare photo featuring V. Biržiška, L. Kisinas, and L. Gira participating in the ceremony when the bibliography was being handed to A. Smetona.L. Kisinas was involved in all the activities run by V. Biržiška, including preparing "Bibliography News," "Lithuanian Encyclopaedia," and so on. While preparing material about the Gipsies, L. Kisinas became acquainted with Gipsy culture and gathered much material not only about their life but also contributed significantly to Gipsy language grammar (this material is preserved by Silvijus, L. Kisinas's son).From 1941 to 1944, L. Kisinas faced many problems due to his origin. It was claimed that he was a Jew and had only adopted Christianity when marrying a Lithuanian girl. In documents, he used to write that he was Lithuanian. This issue also troubled V. Biržiška. However, in 1941, their paths diverged: V. Biržiška left for the West and settled in the USA, while L. Kisinas returned to Lithuania from Germany in 1944-1945.Thus, L. Kisinas is known as one of the most serious culture workers and one of the most productive bibliographers in Lithuania.